23 Number of Levels Appropriately Treated with Vertebral Augmentation (Vertebral Augmentation, 2020)
Vertebral augmentation, such as vertebroplasty and kyphoplasty has been introduced as effective treatment options for vertebral compression fracture. Unfortunately, there are many multiple level fractures in both osteoporotic and metastatic compression fractures. There are also still some questions about the maximum number of levels that should undergo vertebral augmentation. Current guidelines indicate that complications of vertebral augmentation may be amplified when more than three vertebral levels are treated concurrently but this has not been reflected in numerous clinical trials, and some researchers have found that complications such as anemia and new compression fracture did not increase with multiple levels of augmentation. They also suggested that treating all the fractures at once might decrease the patients’ morbidity. In conclusion although the number of compression fracture levels to treat with vertebral augmentation should be based on a meticulous analysis of each individual’s circumstances and many levels can be treated in an attempt to decrease patient morbidity, a generally agreed upon maximum number of levels is three per augmentation session.
Keywords: complications; levels; multiple compression fractures; vertebral augmentation